Upaya Meningkatkan Kemampuan Berhitung melalui Penggunaan Media Ular Tangga Matematika pada Peserta Didik Kelas 2 SD Negeri Glagahombo 1 - Aninda Budi Pawestri; Ari Wibowo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve arithmetic skills through the use of a Snakes and Ladders Mathematics board game as a learning medium. The research was motivated by the low numeracy performance of second-grade students at SD Negeri Glagahombo 1. The teacher plays a crucial role in designing innovative and enjoyable learning strategies that encourage students to engage actively. Before the intervention, the learning success rate was only 50% with an average score of 69,92, which was below the minimum mastery criterion of 75. To address this issue, the researcher and teacher collaborated to implement the "Snakes and Ladders" mathematics instructional tool. This Classroom Action Research was conducted in two cycles. The findings showed that in the first cycle, the success rate increased to 79% with an average score of 78,18. In the second cycle, the success rate reached 100% with an average score of 88,77. The second cycle confirmed that all 24 students achieved the mastery criterion. In conclusion, the application of Snake and Ladder Mathematics successfully enhanced the arithmetic ability of second-grade students at SD Negeri Glagahombo 1.